ANALYSIS OF SUSTAINABILITY INDEX USAHATANI CABAI IN BANGLI REGENCY - Ustriyana, I Nyoman Gede; Artini, Ni Wayan Putu (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.12, No.1, 2018DO - 10.24843/SOCA.2018.v12.i01.p08, 2018)
There are many experts who disagree on the meaning of the concept of sustainable development. Nevertheless sustainable agriculture has been known to be one of important factor in realizing sustainable development. It is therefore very relevant to conduct a research in order to measure the sustainability of agricultural development through sustainability index measurement. In this study analyzed the sustainability is using composite index calculation method. Methods of data collection was conducted through interviews using structured questionnaire survey conducted to total of 60 respondent of chili farmers in Bangli Regency. The calculation results of the sustainability index of 30 variables obtained shows that only 1 variables were categorized as “high”, 20 variables were in “medium” category and 9 variables were in “low” category. From the results obstained the composite index analysis showed a combined index categorized as “medium” with a value of 0.47.